Component Restoration in the Bilateral Intermediate Cleft Tip Rhinoplasty. Issue 2 (27th July 2021) - Dang, Brian N.; Pfaff, Miles J.; Jain, Nirbhay S.; Hu, Allison C.; Bertrand, Anthony A.; Chan, Candace H.; Kang, Vicky; Lee, James C.; Bradley, James P.; Lee, Justine C.
Abstract : Summary: The intermediate cleft tip rhinoplasty is frequently performed during childhood to address nasal tip anomalies in cleft patients before the most critical period of psychosocial development. The authors previously described the component restoration intermediate cleft tip rhinoplasty technique for the unilateral cleft nose, which was developed to systematically address the lining deficiency, cleft lower lateral cartilage malpositioning, and cleft lateral cartilage weakness using a combination of lower lateral cartilage release, lateral cartilage repositioning, and placement of an auricular composite chondrocutaneous graft. In this work, the authors evaluate the utility of this technique to the bilateral cleft nose. Preoperative and postoperative (mean ± SD, 18.6 ± 10.8 months) photographs of bilateral cleft patients treated with the component restoration intermediate cleft tip rhinoplasty ( n = 7) were evaluated using photogrammetric measurements and aesthetic assessments. From preoperatively to postoperatively, the columella length–to–alar width ratio on basal photographs increased (0.19 ± 0.05 versus 0.28 ± 0.05; p = 0.001). On lateral view, the columella-labial angle decreased from preoperatively to postoperatively [138 degrees (interquartile range, 132 to 144 degrees) versus 123 degrees (interquartile range, 122 to 139 degrees); p = 0.04]. Aesthetic ratings performed by four blinded observers also improved from preoperatively to postoperatively (1.6 ± 0.8 versus 2.4 ± 0.7; p = 0.004). As a comparison, bilateral cleft nose patients who did not undergo intermediate cleft tip rhinoplasty ( n = 3) of similar ages were subjected to the same photogrammetric and aesthetic analyses, which showed no differences from preoperatively to postoperatively. In combination, the current work suggests that the component restoration technique in the bilateral intermediate cleft tip rhinoplasty improves nasal tip support and aesthetic outcomes.